A CORRELATIOAL STUDY ON TERTIARY STUDENTS’ READING HABITS AND THEIR CRITICAL READING SKILLS - Iqbal Risca; Rahma Dianti (Language and Education Journal, 2021)
Reading habit influences students’ achievement of reading comprehension. It is assumed that if people have good reading habit, they will have good comprehension toward reading texts. The study was highlighted to examine the association between English education department students’ reading habits and their critical reading skills. This study was conducted using a correlational research design. The population of this study consisted of 112 undegraduate students of English Education department of Tridinanti University in the academic year 2017/2018. There were 37 students participating as the sample of the study chosen by using purposive sampling. In collecting the data, a questionnaire of reading habit and a critical reading test were distributed. A correlational analysis using Pearson Product Moment was applied to seek the association between the variables measured. Based on the data analysis result, it was found that students’ reading habit was not significantly correlated with students’ critical reading skills